'Ordinary decent domestic violence': A discursive analysis of family law judges' interviews. (May 2015) - Naughton, Catherine M; O'Donnell, Aisling T; Greenwood, Ronni M; Muldoon, Orla T
This study examined judges' constructions of the 'best interests of the child' in child custody and access arraignments where there were allegations of domestic violence within the context of an interview. Using interviews with six Irish District Court judges, a micro-structural discourse analysis enabled the identification of socio-cultural discourses, scientific knowledge and judges' own values and beliefs biases about custody arraignments in cases of domestic violence. Judges' discourses were shaped by an idealisation of the nuclear family unit which resulted in a pro-access philosophy (Theme 1). The knowledge that domestic violence had occurred challenged this ideology and, to rhetorically manage this dilemma, judges' talk normalised or trivialised abusive parents' behaviour, which rendered domestic violence irrelevant to child custody and access (Theme 2). Mothers who alleged domestic violence when they disputed contact between fathers and their children were pathologised through talk (Theme 3). It is recommended that systems be put in place, including judicial training, to facilitate judges in their decision-making process in this highly discretionary and complex area of the law.